Peningkatan Fungsi UKS Dalam Memberikan Pendidikan Kesehatan Awal Berbasis IPTEKPada Sekolah Dasar Desa Belatungan - Cahyadi Putra, I Gusti Ngurah Anom; Eka Karyawati, A. A. Istri Ngurah; Raharja, Made Agung; Mastrika Giri, Gst. Ayu Vida; Widiartha, I Made (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 9 No 1 (2020): JELIKU Volume 9 No 1, Agustus 2020DO - 10.24843/JLK.2020.v09.i01.p07, 2020)
Usaha Kesehatan Sekolah (UKS) is a basic health business owned by a school. One of the functions of UKS is as a forum to provide early health education to school children. In primary schools the UKS maggot village does not function optimally, because there are no facilities and infrastructure to support UKS activities. Through the Udayana Mengabdi Program, assistance is provided for facilities and infrastructure, such as first aid kits, weighing instruments, temperature measuring instruments and height measuring instruments. Booked the administration of health records for elementary school students. From the programs that have been implemented, a survey is conducted to measure the success rate. After the service program was conducted the average level of knowledge of students about the function of UKS increased. As well as UKS in elementary schools, it should function properly as a place to provide early health education to elementary school children.